FORMULAÇÕES SEMISSÓLIDAS CONTENDO NANOCÁPSULAS DE ADAPALENO: DETERMINAÇÃO DA ESTABILIDADE, AVALIAÇÃO DA LIBERAÇÃO IN VITRO E ENSAIOS UTILIZANDO BIOMETRIA CUTÂNEA - Farias, Gabriela D'avila (2011)
Acne vulgaris is a genetic hormone disease, located in the hair follicle. Adapalene a third-generation retinoid, and it is a topical alternative for acne treatment, but may have some adverse effects, irritation and dryness of the skin are the most common. Due to this, and knowing the nanocarriers potential, the object of this study was determine the physicochemical stability of semisolid formulations containing adapalene-loaded nanocapsules (NC) incorporated in Aristoflex AVL®, evaluate the release profiles in semisolid formulations containing nanocapsules containing adapalene incorporated in Carbopol 940® and verify the safety of the formulation in vivo by noninvasive biophysical analysis. For the determination of the stability, samples were subjected to freeze-thaw cycle, completing a cycle of 21 days. The in vitro release studies were performed comparing the drug-loaded NC (GCNCA) with the gel containing adapalene in its free form (GCA). For the skin bioengineer techniques, twenty healthy volunteers were selected. Each week were performed biometric skin tests including stratum corneum water content (hydration), pH, color, erythema and transepidermal water loss for 63 days. In stability studies, we observed that the average particle size, polydispersity and zeta potential of cream gel containing NC without adapalene (CGNC) and cream gel containing adapaleneloaded NC (CGNCA) showed no change after being subjected to the freeze-thaw cycle. Semisolid formulations showed non-Newtonian flow and pseudoplastic behavior during the study period. The initial adapalene content in CGNCA did not change compared with the result obtained at the end of the experiment. However, for the cream gel containing free adapalene (CGA), there was a reduction in the drug concentration, whereas the initial content decreased to below 90% after 21 days of analysis. According to release studies, we can observe that the GCNCA showed total concentration and release rate less than the GCA, which demonstrates the ability of nanoparticles to control the drug release. According to the results observed for the non-invasive method in relation to the determination of melanin content, there was a decrease in this parameter during the experiment for both formulations. The GCNCA did not cause erythema, configuring security in the use of the formulation. However, the GCA increased the index of erythema of the skin of volunteers. We observed an increase in transepidermal water loss to the GCA while in GCNCA there is a reduction of this parameter. The results obtained for skin hydration, there was a more pronounced reduction of the values of the stratum corneum water content in the treated areas with GCA. Thus, it was evident that the polymeric nanocapsules are able to decrease transepidermal water loss, favoring the skin hydration degree and keeping the stratum corneum integrity.